CEO Overconfidence and Management Forecasting - HRIBAR, Paul (Institutional Knowledge at Singapore Management University, 2016)
This paper examines how overconfidence affects the properties of management forecasts. Using both the ‘over‐optimism’ and ‘miscalibration’ effects of overconfidence to generate our predictions, we examine three research questions. First, we examine whether overconfidence increases the likelihood of issuing a forecast. Second, we examine whether overconfidence increases the amount of optimism in management forecasts. Third, we examine whether overconfidence increases the specificity and precision of the forecast. We use both options‐ and press‐based measures to proxy for individual overconfidence, and find support for all three research questions. We further find that the results are concentrated among firms that provide forecasts sporadically, consistent with overconfidence playing a stronger role when managers have more flexibility in determining forecast properties.